ANALISIS REDUKSI HARMONISA (STUDI KASUS POWER QUALITY DI PDS LINE 1 STASIUN ASEAN MRT JAKARTA) - Nugraha, Alfikri Raihan; Suryanto, Agus (Universitas 17 Agustus 1945 Jakarta, 2025)
This research is taken as a case study related to harmonic reduction at the ASEAN Station MRT Jakarta. ASEAN Station has a non-traction substation or PDS (power distribution system) which functions as a power supply for electrical and signaling purposes. PDS line 1 ASEAN Station has a THDi value that is not in accordance with the safe standard of IEEE 519-2014 which is 8%. Therefore, an analysis is needed to reduce harmonics by using a single tuned passive filter in ETAP software, considering that currently there is no harmonic filter installed. From power quality data in the field for 3 days, it was found that the highest harmonic disturbance was in phase R on Tuesday (2/7/2024). The average THDi is 39.90% and THDv is 1.16% with negative or leading power factor characteristics. The results showed that the single tuned passive filter was able to reduce harmonics at the highest contributing orders (orders 5, 7, and 11) in the ETAP simulation with THDi reduction effectiveness of 91.81% on Tuesday (2/7/2024), 91.62% on Wednesday (3/7/2024), and 90.01% on Thursday (4/7/2024). As for THDv, it was 76.16% on Tuesday (2/7/2024), 75.85% on Wednesday (3/7/2024), and 74.77% on Thursday (4/7/2024). However, the installation of this filter is less effective or not recommended in the characteristics of capacitive loading (leading) in PDS line 1 ASEAN Station because it results in a decrease in power factor to 0.48 (leading).